Il circolo virtuoso tra regional brand e attrattività Regionale: prime evidenze dalle regioni italiane - Passeri, Riccardo; Mazzi, Chiara; Viassone, Milena (Piccola Impresa / Small Business, 2014)
The objective of the present work is twofold: first it aims at investigating the relationship between a regional attractiveness index (RAI) and a regional brand index (RBI); second, it classifies Italian regions based on the two indices. The regional attractiveness depends on 10 key-drivers, while the regional brand on 7 key-drivers and there is a significant relationship between these two indices, confirming the existence of a virtuous circle between RAI and RBI. This paper identifies 4 clusters of Regions: diamond point, evergreen, nursery and rough stone. Finally, we suggest strategies in order to maximise the level of the two indices. Although this paper is an explorative research, we give precious hints for further applications of the two indices at different regional levels, allowing a cross-country comparison